Parental residential and partnering transitions and the initiation of adolescent romantic relationships - Ivanova, K; Mills, M; Veenstra, R (Wiley, 2014)
This study focused on the possible links between parental residential and partnering transitions (a parent's move out of the household, introduction of a new maternal and paternal partner) and the initiation of romantic relationships in adolescence. Using data from a prospective cohort study of Dutch adolescents (the TRacking Adolescents' Individual Lives Survey; N = 1,513), recurrent event discrete‐time models with random effects were estimated, controlling for the initial family structure and quality of family climate. The results demonstrated that when all 3 events were considered, only the initiation of a new romantic relationship by the mother was associated with an increase in the odds of initiating a romantic relationship for the adolescent.